Identification of oropharyngeal squamous cell carcinomas with active HPV16 involvement by immunohistochemical analysis of the retinoblastoma protein pathway - Holzinger, Dana; Flechtenmacher, Christa; Henfling, Nataly; Kaden, Ines; Grabe, Niels; Lahrmann, Bernd; Schmitt, Markus; Heß, Jochen; Pawlita, Michael; Bosch, Franz X. (International journal of cancer, 2013)
Viral oncogene RNA expression is regarded as reliable biomarker to identify oropharyngeal squamous cell carcinomas (OPSCC) with active HPV16 involvement. This study addressed whether the expression profile of the cellular proteins p16INK4a, pRb, Cyclin D1 and p53 provide surrogate marker combinations that identify OPSCC with active HPV16 in situations where only formalin-fixed biopsies are available. Protein expression was analyzed by immunohistochemistry on tissue microarrays created from 188 OPSCC of which the HPV16 DNA and RNA status had been established previously from snap-frozen biopsies. Associations of single markers and of marker combinations with HPV16 DNA, viral RNA expression patterns and overall survival as primary end point were evaluated by statistical analysis. Most tumors with active HPV16 involvement (RNA+ group; n = 40) showed a specific protein pattern, that is, high p16INK4a (80%), low pRb (85%), low Cyclin D1 (95%) and normal p53 (73%). This pattern was significantly different from the pattern observed in HPV DNA-negative tumors (HPV- group) and in HPV16 DNA-positive tumors lacking viral RNA expression patterns (RNA- group). The combination of high p16INK4a and low pRb levels was distinctly superior to p16INK4a alone; it was strongly associated with RNA+ tumors (OR 41.4, 95%CI 10.7-162.5), with improved survival (HR 0.37, 95%CI 0.2-0.8) and had best predictive values (78% sensitivity, 93% specificity, 78% PPV, 93% NPV). In conclusion, if only formalin-fixed biopsy material is available, the marker combination high p16INK4a/low pRb is well suited to identify OPSCC with biologically active HPV16 which represent a distinct OPSCC entity with improved prognosis.